Multidisciplinary management of a fused maxillary incisor: Case report with 5‐year follow‐up - El Backly, Rania M. (Clin Case Rep, 2020)
Detailed treatment planning and execution are crucial if regenerative approaches are to be attempted to retain fused permanent teeth. Long‐term follow‐up is necessary to monitor the stability of the final outcome, both esthetically and functionally.